TAX REVENUE AND RETRIBUTION OF SAMARINDA CITY ON LOCAL REVENUE - Pamungkas, Giantoro (Journal of Industrial Engineering & Management Research, 2023)
Tax and levy collection is a significant source to support regional improvement. Tax and levy realization contributed an average tax of 114.6% and the realization of retribution contributed an average retribution of 94.83%. Revenue per type of tax is largest by street lighting tax with an average revenue of Rp. 111,202,687,441 and the lowest by billboard tax with an average revenue of Rp. 7,747,613,232. Realization per type of retribution was greatest for the general services retribution with average revenue of Rp. 28,203,392,665 and least for the business services permit retribution with average revenue of Rp. 4,517,555,842. Samarinda City Original Revenue (PAD) in 2020 amounted to Rp. 485,143,157,813 and in 2019 amounted to Rp. 560,679,282,249.